The impact of free trade agreements on business activity: A survey of firms in the People's Republic of China - Yunling Zhang (Asian Development Bank Institute (ADBI), 2010)
The People's Republic of China (PRC) has emerged as a major player in the global economy and considers free trade agreements (FTAs) an important part of its global trading strategy. The PRC's export industries are embedded in existing regional and global production networks and are reliant on foreign direct investment flows and external supplies of material and intermediate goods. Immediately after its accession to the World Trade Organization in December 2001, the PRC adopted a regional approach to trade and began negotiating and implementing FTAs. This paper analyzes the results of a survey undertaken across 232 Chinese firms with regard to FTA-related issues such as utilization, perceived costs and benefits, perceptions of multiple rules of origin, and policy and institutional support mechanisms. It was found that, of the firms surveyed, 45% were using FTAs to some extent. While this utilization rate appears relatively high, and reflects the assertive stance of Chinese firms when it comes to exploring market opportunities, the actual coverage of export value by FTAs is variable. In general, Chinese firms view FTAs as a way to increase their access to partner markets. Nevertheless, there remains an orientation toward the United States and other traditional markets. However, over time, as rebalancing of growth takes place, there may be a shift in market orientation toward the Association of Southeast Asian Nations (ASEAN) and regional markets and the use of FTAs may intensify. This study offers several proposals to increase FTA use, including the expansion of support services for firms, the promotion of larger regional FTAs, and the creation of more opportunities for collaboration between the government and the private sector.
Keywords: F1; F15; O24; 330; Außenhandelsliberalisierung; Handelsabkommen; Wirtschaftliche Anpassung; Außenhandelseffekt; China